Room temperature, liquid-phase Al2O3 surface coating approach for Ni-rich layered oxide cathode material. Issue 15 (30th January 2019) - Neudeck, Sven; Strauss, Florian; Garcia, Grecia; Wolf, Hannes; Janek, Jürgen; Hartmann, Pascal; Brezesinski, Torsten
Abstract : Solution-based trimethylaluminum treatment of NCM811 cathode material leads to drying and coating in a single step and therefore improved cycling performance. Abstract : A room temperature, atomic-layer-deposition-like coating strategy for NCM811 (80% Ni) is reported. Trimethylaluminum is shown to readily react with adsorbed moisture, leading both to Al2 O3 surface layer formation on NCM811 and to trace H2 O removal in a single treatment step. Even more importantly, the cycling performance of pouch cells at 45 °C is greatly improved.